Pengasuhan dan Pengangkatan Anak Berdasarkan Ketetapan Aturan yang Berlaku di Indonesia - Nurul ‘Izzah HD; Tharisya Putri Ramadhani; Desy Pardilawati; Siti Indri Permatasari (Jurnal Hukum dan Sosial Politik, 2025)
Parenting and Child Adoption are crucial aspects of child protection implementation. This article explains suitable parenting patterns for parents to apply to their children. It also highlights child adoption as a subsequent step when no party is responsible for the child's custody. Adoption involves the legal transfer of parental responsibilities and custody from child’s biological family to the adoptive family. There are procedures for carrying out the adoption of a child which must be observed and complied with as outlined by legal regulations. This is intended to safeguard and uphold the child’s rights overall welfare.